Common Toxic Plants for Florida Horse Owners - Alyssa Schortinghouse; Brent Sellers (EDIS, 2023)
This publication is intended to provide horse owners with critical information about common toxic plants encountered in Florida. Written by Alyssa Schortinghouse and Brent Sellers, and published by the UF/IFAS Veterinary Medicine—Large Animal Clinical Sciences Department, January 2023.